Implications of Space Exploitation and Exploration on The Environment by Human Rights - Ahmad Syahird; Irwan (Universitas Muhammadiyah Surabaya, 2023)
This study aims to require an instrument of international law on the laws of space which is an ecological perspective by including the right to get a good and clean environment for everyone. Then, it will need to be found in the application of international-law instruments that have existed by launcher and private states to engage exploitation and exploration activities in space. This type of study results in normative juridical research that guides current international laws and regulations and other legal materials by studying library materials of legal materials that are relevant to the topic. The results of this study suggest that the destruction of exploitation and space exploration is a structural problem due to the political economic domination, both of developed and private countries and capital. By power and capital superiority, the exploitation and exploration of space are done far away from the perspective of human rights.